Analisis Pengeluaran Pemerintah Terhadap Human Development Index (Hdi) di Indonesia - Yuniarti Reny Renggo (Universitas Kristen Wira Wacana Sumba, 2013)
The aim of this study was to analyze the influence of government expenditure in educational, health and infrastructure sector on Human Development Index (HDI) in Indonesia. The government expenditure in infrastructure is proxied by the variable of the government infrastructure expenditure in housing and public facility. The government expenditures in education, health and infrastructure sectors are investment in Human Development Index. The research used panel regression ie Fixed Effect model approach. The result of this resarch is that the government expenditure in health sector has positive influence in developing Human Development Index in Indonesia. However, the government expenditures in education and infrastructure doesn’t have significant impact on HDI.